C9orf72 associates with inactive Rag GTPases and regulates mTORC1‐mediated autophagosomal and lysosomal biogenesis. Issue 4 (25th February 2020) - Wang, Mingmei; Wang, Hongfeng; Tao, Zhouteng; Xia, Qin; Hao, Zongbing; Prehn, Jochen H. M.; Zhen, Xuechu; Wang, Guanghui; Ying, Zheng
Abstract: GGGGCC repeat expansion in C9orf72 is the most common genetic cause in both frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), two neurodegenerative disorders in association with aging. Bidirectional repeat expansions in the noncoding region of C9orf72 have been shown to produce dipeptide repeat (DPR) proteins through repeat‐associated non‐ATG (RAN) translation and to reduce the expression level of the C9orf72 gene product, C9orf72 protein. Mechanisms underlying C9orf72 ‐linked neurodegeneration include expanded RNA repeat gain of function, DPR toxicity, and C9orf72 protein loss of function. In the current study, we focus on the cellular function of C9orf72 protein. We report that C9orf72 can regulate lysosomal biogenesis and autophagy at the transcriptional level. We show that loss of C9orf72 leads to striking accumulation of lysosomes, autophagosomes, and autolysosomes in cells, which is associated with suppressed mTORC1 activity and enhanced nuclear translocation of MiT/TFE family members MITF, TFE3, and TFEB, three master regulators of lysosomal biogenesis and autophagy. We demonstrate that the DENN domain of C9orf72 specifically binds to inactive Rag GTPases, but not active Rag GTPases, thereby affecting the function of Rag/raptor/mTOR complex and mTORC1 activity. Furthermore, active Rag GTPases, but not inactive Rag GTPases or raptor rescued the impaired activity and lysosomal localization of mTORC1 in C9orf72‐deficient cells. Taken together, the present study highlights a key role of C9orf72 in lysosomal and autophagosomal regulation, and demonstrates that Rag GTPases and mTORC1 are involved in C9orf72‐mediated autophagy. Abstract : Pathogenic mutation in C9orf72 is the most common cause of frontotemporal dementia and amyotrophic lateral sclerosis. Loss of C9orf72 protein will decrease the activity of Rag GTPases and mTOR lysosomal localization. C9orf72 mediates autophagosomal and lysosomal biogenesis through Rag GTPase‐mTORC1‐MITF/TFE3/TFEB signaling axis.